CERAMIC MEMBRANE FILTERS: MANUFACTURING OF MICRO/NANOPOROUS MEMBRANE ELEMENTS - P.A. VITYAZ; О.А. PROKHOROV; V.M. SHELEKHINA; L.P. PILINEVICH (Advanced Engineering Research)
The present paper introduces to research and development of ceramic membrane filters with gradient micro/nanoporous (30-300 nm) structure.